2016
DOI: 10.1111/hae.12936
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers of haemophilic arthropathy: correlations with compatible additive magnetic resonance imaging scores

Abstract: Introduction: Although biomarkers are useful diagnostic tools to assess joint damage in osteoarthritis and rheumatoid arthritis, few data exist for biomarkers of haemophilic arthropathy. Aim: To evaluate the association between biomarkers and compatible additive magnetic resonance imaging (MRI) scores in patients with severe haemophilia A. Methods: Patients aged 12-35 years with no history of factor VIII (FVIII) inhibitors were enrolled in a controlled, cross-sectional, multinational investigation. Patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…On the contrary, a different study found no strong correlation between the same biomarkers and radiological and physical examination of the joint [ 34 ]. Oldenburg et al did not confirm the correlations for serum CS846 and X-ray parameters, on the contrary they found a significant correlation of serum CS846 with MRI score in a small subpopulation [ 45 ]. The relationship of serum cartilage oligomeric matrix protein (COMP) with arthropathy was evaluated in five studies with different results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, a different study found no strong correlation between the same biomarkers and radiological and physical examination of the joint [ 34 ]. Oldenburg et al did not confirm the correlations for serum CS846 and X-ray parameters, on the contrary they found a significant correlation of serum CS846 with MRI score in a small subpopulation [ 45 ]. The relationship of serum cartilage oligomeric matrix protein (COMP) with arthropathy was evaluated in five studies with different results.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship of serum cartilage oligomeric matrix protein (COMP) with arthropathy was evaluated in five studies with different results. Two studies reported a significant positive association of COMP with JSN on the X-ray while three other studies reported weak negative or no correlations with the severity of HA on the imaging [ 34 , 45 , 60 , 61 , 62 ]. The serum level of COMP was studied in three different studies with contradictory results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of soluble biomarkers, including C-terminal telopeptides of type I collagen, cartilage oligomeric matrix protein, TIMP-1, MMP-3, MMP-9, VEGF, and CS846, with these symptoms in hemophilia A have been investigated, but no obvious associations between these soluble biomarkers and MRI joint scores have been reported, except for the positive association of CS846 with MRI joint sores in Oldenburg study. The joint arthropathy in hemophilia A is not a systemic disease, so the analysis of biomarkers of joint arthropathy may be more complex than in RA and OA [31] ; multiple biomarkers can perhaps more effectively and accurately detect the severity of joint arthropathy. Furthermore, whether soluble CS846 and sVCAM-1 levels increase at the same time points or at different time points in hemophilic arthropathy is worth investigating.…”
Section: Discussionmentioning
confidence: 99%